The Impact of a Dynamic Task Environment: A Study of Architectural-Engineering Firms - Brown, Warren B. (Academy of Management Journal, 1969)
This study focuses on architectural-engineering firms and the organizational impact on them caused by major dynamic shifts in their task environment. Diverse organizational strategies by these firms are examined, along with their implications for the viability of such groups.